1996
DOI: 10.1002/j.1460-2075.1996.tb00949.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the PU.1 gene results in multiple hematopoietic abnormalities.

Abstract: PU.1 is a member of the ets family of transcription factors and is expressed exclusively in cells of the hematopoietic lineage. Mice homozygous for a disruption in the PU.1 DNA binding domain are born alive but die of severe septicemia within 48 h. The analysis of these neonates revealed a lack of mature macrophages, neutrophils, B cells and T cells, although erythrocytes and megakaryocytes were present. The absence of lymphoid commitment and development in null mice was not absolute, since mice maintained on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
779
1
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,029 publications
(804 citation statements)
references
References 76 publications
(65 reference statements)
18
779
1
6
Order By: Relevance
“…Microglia belong to the hematopoietic lineage, as evidenced by microglia loss in Pu.1 knockout mice, which lack a transcription factor required specifically in hematopoietic cells [14]. Microglia progenitors enter the CNS at embryonic day 9.5-10.5 [1,2], prior to the emergence and differentiation of other nervous system glial-cell types, and consistent with their critical role in shaping CNS development.…”
Section: The Role Of Microglia In Cns Developmentmentioning
confidence: 81%
“…Microglia belong to the hematopoietic lineage, as evidenced by microglia loss in Pu.1 knockout mice, which lack a transcription factor required specifically in hematopoietic cells [14]. Microglia progenitors enter the CNS at embryonic day 9.5-10.5 [1,2], prior to the emergence and differentiation of other nervous system glial-cell types, and consistent with their critical role in shaping CNS development.…”
Section: The Role Of Microglia In Cns Developmentmentioning
confidence: 81%
“…One strain of PU.1 knock out mice shows defects in erythroid maturation (Scott et al, 1994). Another PU.1 de®cient mouse strain exhibits no apparent defects in erythrocyte development but are de®cient in macrophages, neutrophils, B cells, and T cells compared to wild-type mice (McKercher et al, 1996;Scott et al, 1997). In both strains, however, the Nterminal half of the PU.1 gene is intact in the targeted genome, and in neither case has it been determined whether the N-terminal peptide is expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Spi-1/PU.1 plays an essential role in normal lymphopoiesis and myelopoiesis. It regulates the transcription of many myeloid and B lymphoid genes (for review Moreau-Gachelin, 1994) and its inactivation in mice results in a multilineage defect characterized by an absence of B lymphocytes and macrophages (McKercher et al, 1996;Scott et al, 1997). Although the down regulation of spi-1 during the chemicallyinduced di erentiation of Friend cells suggested that Spi-1 was involved in the di erentiation arrest of the proerythroblast (Schuetze et al, 1992), the role of Spi-1/PU 1 in the transformation of erythroid cells was deduced from the pathology observed in mice overexpressing a spi-1 transgene (Moreau-Gachelin et al, 1996).…”
Section: Introductionmentioning
confidence: 99%